The University after obtaining its license - Zevallos Acosta, Uladislao (2019)
The University is a place of discussion and debate; an open space where all ideas contend and exhibit their contradictions. It is the gateway to knowledge, where everything we feel and believe in can be expressed, can be objectified without fear and where the only decision-making tool is reasoning. It is also worth taking into account the paradigm of Singularity University, created by NASA and Google in 2009, which has already broken with the traditional model of studies, having as its sole objective to train leaders or world leaders (Vásquez, 2017).